2023
DOI: 10.1186/s40510-023-00454-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress and movement trend of lower incisors with different IMPA intruded by clear aligner: a three-dimensional finite element analysis

Abstract: Background During the intrusion of lower incisors with clear aligners (CAs), root disengagement from the alveolar bone often occurs, resulting in serious complications. This study aimed to determine the potential force mechanism of the mandibular anterior teeth under the pressure of CA, providing theoretical data for clinical practice. Methods In this study, a 3D finite element model was established, including the CA, periodontal ligament, and mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The appropriate direction for intrusion, which maintained the vertical position of incisors, was consistently 10° labial to the long axis of incisors. Likewise, another FEA analysis [32] revealed that as the IMPA increased from 90° to 110°, the moment of mandibular central incisors changed from a lingual crown moment to a labial crown moment. Additionally, an intrusion force of approximately 50-100 g per side have been proved effective and safe [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…The appropriate direction for intrusion, which maintained the vertical position of incisors, was consistently 10° labial to the long axis of incisors. Likewise, another FEA analysis [32] revealed that as the IMPA increased from 90° to 110°, the moment of mandibular central incisors changed from a lingual crown moment to a labial crown moment. Additionally, an intrusion force of approximately 50-100 g per side have been proved effective and safe [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…In clear aligner treatment, when the anterior teeth are intruded with the aligner, the posterior teeth will be extruded as anchorages [ 14 , 30 ]. In order to improve the intrusion efficiency and prevent the CA from off-tracking, it is necessary to design retention attachments on the posterior teeth [ 14 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clear aligner treatment, when the anterior teeth are intruded with the aligner, the posterior teeth will be extruded as anchorages [ 14 , 30 ]. In order to improve the intrusion efficiency and prevent the CA from off-tracking, it is necessary to design retention attachments on the posterior teeth [ 14 , 30 ]. This study found that, when mini-implant anchorage was used, there still existed off-tracking tendencies of the CA at the posterior teeth, which should be paid attention to in clinical practice and more retention attachments should be designed if necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the finite element (FE) model, the periapical bone was established as a fixed constraint, the interfaces between the dentition and periodontium, periodontium and alveolar bone, and attachment and dentition were set as fixed contacts. Additionally, the relationships between the clear aligner and dentition, as well as between adjacent teeth, were configured as sliding frictional contacts, with a friction coefficient of 0.2 based on prior research 14 , 15 .…”
Section: Methodsmentioning
confidence: 99%